GAMBARAN MENGUNYAH BUAH APEL DAN BUAH MELON TERHADAPPENURUNAN DEBRIS INDEKS PADASISWA/I KELAS 2 SMP N 7 KISARAN - Yenny Lisbeth Siahaan; Ni Made Yuliana; Rifkia Amel Azhima (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Debris is a soft mineral that sticks to teeth, usually stuck in between teeth and is a contributing factor to the formation of dental caries and tartar. Debris can only be cleaned by brushing your teeth and consuming fibrous foods. Fiber foods have good teeth-cleaning power, found in fruits such as apples and melons. Chewing fruit will increase saliva and help rinse teeth from stuck food debris. Apples and melons are fruits that contain high fiber. This type of research was descriptive research using the Debris Index examination method directly in the oral cavity. The sample in this study was 30 students in Class 2 of SMP N 7 Kisaran. The research results showed that before chewing an apple, none of the respondents had good Debris Index criteria, 80% had moderate criteria and 20% had poor criteria. Before chewing melon, none of the respondents had good Debris Index criteria, 60% had moderate criteria and 40% had poor criteria. After chewing an apple there was a 100% Debris Index in good criteria. After chewing melon, respondents who had a Debris Index with good criteria were 66.67%, with moderate criteria 33.33% and none had bad criteria. It can be concluded that chewing apples and melons can reduce the Debris Index number. The decrease in Debris Index after chewing apples was 1.22 on average and after chewing melons, it was 1.21 on average. It is hoped that students regularly consume fruit that contains lots of fiber such as apples and melons.